AN EVALUATION OF THE USE OF ONLINE PROGRAMMING SIMULATOR TO INCREASE THE PARTICIPATION RATE OF CLASSROOM STUDENT ATTENDANCE - Sahara, Riad; Abdullah, Syahid; Ramadhona Hassolthine, Cian; Ikhwani Saputra, Muhammad (Jurnal PTK dan Pendidikan, 2024)
The Informatics Distance Learning Study Program at UNSIA is one of the study programs that employs a significant number of practicum-type courses as part of its learning process. The implementation of the practicum is carried out through joint simulations to achieve 21st-century graduate competencies. The implementation of learning for practicum-type courses is carried out through the utilization of the Learning Management System (LMS) and zoom. In practicum-type courses, students are required to install the software necessary for the lecture process, particularly for joint simulations. A significant number of students have encountered difficulties in installing the requisite software. These issues led to a dearth of student engagement during the joint simulations conducted via Zoom, particularly in terms of active participation. The implementation of an appropriate online programming simulator (OPS) is expected to enhance participation in practicum-type courses during synchronous sessions, thereby facilitating the acquisition of the greatest possible learning. The results of the analysis conducted before the implementation of OPS revealed that the lowest active class participation rate was 36.7% (22 students) out of a total of 60 students, while the highest active class participation rate was 50.0% (30 students) out of a total of 60 students. Following the implementation of OPS, the lowest participation rate was 83.3% (53 students) of the total 60 students, while the highest active class participation rate reached 96.7% (58 students) of the total 60 students. Keywords: Class Participants, E-Learning, Higher Education, Online Programming Simulator